Personal, Relationship, and Professional Indicators: A Holistic Approach to Assess Satisfaction and Success in Life - Kolliyil, Abdul Rashid (Global journal of Business and Integral Security, 2024)
This research delves into the intricate nature of life satisfaction and success, tracing the historical evolution of concepts from the 17th century to the present. The study highlights the paradigm shift from materialism to a post-materialistic perspective, culminating in the contemporary emphasis on subjective social indicators. Through an extensive literature review, the research identifies a crucial gap in existing scholarship – the lack of integration of personal, relationship, and professional elements into a comprehensive framework for assessing life satisfaction. The first objective investigates the interconnected factors influencing the satisfaction and success of individuals. A comprehensive exploration unfolds, revealing the dynamic interplay of personal, relationship, and professional dimensions. The study delves into multifaceted influences, including psychological foundations, health, personal development, social factors, environment, education, career, and economics. Through scholarly studies and real-world examples, the profound impact of various factors on satisfaction and success is illuminated, emphasizing the importance of a balanced approach. The second objective introduces a groundbreaking life satisfaction metric, the Personal, Relationship, and Professional (PRP) Index. The rationale, methodology, and components of this tool are presented for a comprehensive assessment of an individual’s well-being. The PRP serves as a proxy for life satisfaction, ranging from zero to one. Subsequent chapters will explore the implementation and validation of the index through empirical data and thorough analyses. The third objective examines the transformative impact of PRP training on life satisfaction. The Experimental Group’s positive shifts post-training underscore the program’s influence on personal well-being, interpersonal dynamics, and professional satisfaction. Noteworthy positive impacts on specific age groups and genders emphasize the program’s efficacy, and nuanced analysis adds depth to our understanding, highlighting the need for tailored interventions. Contrasting with the Control Group, the Experimental Group’s significant increase in PRP Index scores attests to the program’s efficacy, reinforcing its impact on personal, relationship, and professional dimensions of life satisfaction. The research underscores the importance of demographic nuances in crafting targeted interventions for a tailored approach to well-being. The final objective analyzes the personal, relationship, and professional characteristics of successful individuals through case studies. Using a holistic approach and case study methodology, the lives of renowned personalities, including Gandhi, Nelson Mandela, APJ Abdul Kalam, and Barack Obama, are explored. Findings reveal a notably high PRP index for each individual, indicating that their success was influenced by a harmonious interplay of personal, relationship, and professional elements. The research contributes to academic understanding and provides practical insights for individuals seeking fulfillment and achievement, aiming to inspire and guide individuals on their own journeys toward fulfillment and success.